Effect of bargaining on pricing and retailing under a green supply chain management. (July 2023) - Davoudi, Zahra; Seifbarghy, Mehdi; Sarkar, Mitali; Sarkar, Biswajit
Abstract : Nowadays, bargaining is increasing with the enlargement of supply chain business globally. It has attracted practitioners' and academicians' attention and has led to a global supply chain formation. Besides, other factors, such as marketing expenditures, significantly impact attracting customers and increasing sales. Due to supply chain members' concerns about optimizing their profits, contracts' usage has surged. The proposed study examines a two-echelon green supply chain with two problems. The first problem consists of a non-linear function of the retailing price with bargaining and greening level of the sold product for market demand. The second problem, retail marketing expenditure for the supply chain management's total profit, is assessed for centralized and decentralized models. Both models are solved through game policy. The analytical derivations give several insightful results on the amount of the green level. It is found that using bargaining can increase the greening level of products and the overall profit, and the marketing expenditure meets the industry's requirements. Numerical studies prove that this study converges over the literature on the greening level of products.